Potential use of plastic waste as construction materials: Recent progress and future prospect - Kamaruddin M.A.; Abdullah M.M.A.; Zawawi M.H.; Zainol M.R.R.A. (Institute of Physics Publishing, 2023)
Concrete mixtures; Concretes; Mixtures; Consumer packaging; Exponential increase; Future prospects; Plastic consumption; Plastic wastes; Recent progress; Research papers; Plastic products